Belgian experience with triple therapy with boceprevir and telaprevir in genotype 1 infected patients who inject drugs. Issue 1 (21st July 2015) - Arain, A.; Bourgeois, S.; de Galocsy, C.; Henrion, J.; Deltenre, P.; d'Heygere, F.; George, C.; Bastens, B.; Van Overbeke, L.; Verrando, R.; Bruckers, L.; Mathei, C.; et al.
Abstract : No data have been reported yet on treatment outcome in persons who inject drugs (PWID) infected with hepatitis C virus treated with boceprevir or telaprevir in combination with peginterferon (Peg IFN) and ribavirin (RBV). Additionally, there are concerns about the safety of boceprevir and telaprevir in some subgroups of patients with hepatitis C (HCV). In a cohort of HCV patients infected with genotype 1 in Belgium, treatment outcome of patients infected due to IV drug use was analyzed and compared with patients who have no history of substance use. The study population consisted of 179 patients: 78 PWID and 101 controls treated with boceprevir (n = 79) or telaprevir (n = 100) additional to Peg IFN and RBV; 53 (30%) had advanced disease (F3, F4) and 79 (44%) had an antiviral therapy previously. There were no significant differences in the baseline characteristics between both groups, except that PWID patients were more frequently infected with genotype 1a (67% vs 21%), were younger and were predominantly male. Psychiatric complaints during follow‐up occurred more frequently in the PWID patients: 24% versus 11% ( P = .02). Treatment failure for other reasons than absence of viral response was 70% and 64% in PWID and non‐PWID respectively. The sustained viral response (SVR) rates were similar in both groups (71% in PWID vs 72% in non‐PWID); with a non‐inferiority test with −5% margin there is a difference of −1% (95% CI [−15%, 13%]) and P = 0.30. There are no reasons to exclude PWID from treatment with boceprevir, telaprevir and novel antiviral therapies. J. Med. Virol. 88:94–99, 2016 . © 2015 Wiley Periodicals, Inc.